THE THERAPEUTIC POWER OF MUSIC IN CONTEMPORARY CHINESE SOCIETY - Ping Su (Journal of Dharma, 2025)
Musicality is a vital practice for becoming the voice of the voiceless in marginalized communities. It extends beyond instruments merely labelled as drums and bells, embodying instead the art of restoring harmony to a broken world. This paper argues that musicology, in any cultural setting, offers a profound pathway toward social prosperity. Unlike contemporary Western music, Chinese musical traditions are deeply rooted in a selfless aspiration to exemplify moral and cultural excellence through performance. This research explores how music fosters hope, healing, and peace, particularly through the act of attentive listening. It examines methods of cultivating harmony via musicology, engaging with the diverse artistic expressions found in the Chinese context. The study traces the historical foundations of Chinese music, drawing upon literary sources—especially those informed by Confucian principles—and evaluates the balance between theory and practice within this tradition. Emphasis is placed on practice as the transformative element, surpassing mere theoretical engagement. Finally, the discussion turns to the challenges of the technological age, where a blurred, fragmented world compels reimagining musicology not merely as academic inquiry but as a therapeutic and transformative practice capable of renewing hope, fostering healing and nurturing peace.